The Relationship between Promotion and Purchase Decision at the Juragan Mode Shop Bengkulu - Amrullah Amrullah (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the relationship between promotions and purchasing decisions at juragan mode shop bengkulu. The analytical methods used in this research are Qualitative analysis and quantitative analysis. From the analysis of the distribution of the average respondents' answers, it shows that the promotion is in the class interval / range 3.41 - 4.20 (good), while purchasing decisions are in the class interval / range 3.41 - 4.20 (good). The value of the correlation coefficient rho (ρ) = 0.69 indicates a strong (close) relationship between the X variable (promotion) and the Y variable (purchase decision). For hypothesis testing, the value of count = 0.69 and table = 0.648. The value of count is greater than table (0.69 > 0.648), this means that Ho is rejected and Ha is accepted, meaning that there is a positive and significant relationship (strong/close) between promotions and purchasing decisions at juragan mode shop bengkulu.